2020
DOI: 10.1177/2150132720932017
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Psychosocial Needs of Patients Being Treated for Opioid Use Disorder in a Primary Care Residency Clinic

Abstract: Purpose: Primary care is an ideal setting to deliver efficacious treatments for opioid use disorder (OUD). Primary care providers need to be aware of other concerns patients with OUD might have in order to provide comprehensive care. This study describes the prevalence of mental health, comorbid substance use, and psychosocial concerns of patients seeking treatment for OUD in primary care and their relation to 6-month treatment retention. Methods: Patients (N = 100; M age = 34.9 years (SD = 10.8), 74% white, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Specifically, in the United States, 13.8% with serious mental illness and 8.8% with any mental illness misused opioids in the past year compared to 2.5% in adults without mental illness [2]. Because of these impairing, widespread, and numerous comorbidities, many groups of clinicians have suggested that, at the very least, access to screening and treatment of these comorbidities in individuals with OUD is important for improving overall health and likely opioid treatment success [6,11,13]. From our experience and perspective, there is a need for integrated, comprehensive interventions-that take into account all co-existing comorbidities-in order to effectively treat OUD.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in the United States, 13.8% with serious mental illness and 8.8% with any mental illness misused opioids in the past year compared to 2.5% in adults without mental illness [2]. Because of these impairing, widespread, and numerous comorbidities, many groups of clinicians have suggested that, at the very least, access to screening and treatment of these comorbidities in individuals with OUD is important for improving overall health and likely opioid treatment success [6,11,13]. From our experience and perspective, there is a need for integrated, comprehensive interventions-that take into account all co-existing comorbidities-in order to effectively treat OUD.…”
Section: Introductionmentioning
confidence: 99%
“…inpatient treatment, criminal justice, population surveys) 60 , 61 or already registered in a SUD treatment program. 36 , 40 , 41 …”
Section: Discussionmentioning
confidence: 99%
“…inpatient treatment, criminal justice, population surveys) 60,61 or already registered in a SUD treatment program. 36,40,41 There have been prior studies estimating the prevalence of dual diagnoses. Kidorf et al 40 found that 48% of individuals who injected opioids had a dual mental health diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations